2004
DOI: 10.1128/jvi.78.17.9352-9365.2004
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine Inhibits Activation of Promoters in Herpes Simplex Virus Type 1 Genomes Independently of Promoter-Specific Factors

Abstract: Flavopiridol, roscovitine, and other inhibitors of Cyclin-Dependent Kinases (CDK) inhibit the replication of a variety of viruses in vitro while proving nontoxic in human clinical trials of their effects against cancer. Consequently, these and other Pharmacological CDK inhibitors (PCIs) have been proposed as potential antivirals. Flavopiridol potently inhibits all tested CDKs and inhibits the transcription of most cellular and viral genes. In contrast, roscovitine and other purine PCIs inhibit with high potenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 89 publications
2
61
0
Order By: Relevance
“…Accordingly, FIT-039 reduced the expression levels of HSV-1 IEGs and early and late genes ( Figure 2B and Supplemental Figure 4). IEGs are transcribed immediately after the viral infection, and their encoded proteins regulate the transcription of early and late viral genes (30). These results indicated that the antiviral mechanism may be attributed to the inhibition of the viral transcription through suppression of the CTD phosphorylation of RNA polymerase II.…”
Section: Introductionmentioning
confidence: 82%
“…Accordingly, FIT-039 reduced the expression levels of HSV-1 IEGs and early and late genes ( Figure 2B and Supplemental Figure 4). IEGs are transcribed immediately after the viral infection, and their encoded proteins regulate the transcription of early and late viral genes (30). These results indicated that the antiviral mechanism may be attributed to the inhibition of the viral transcription through suppression of the CTD phosphorylation of RNA polymerase II.…”
Section: Introductionmentioning
confidence: 82%
“…2 D and E). We therefore tested entry using reporter cells containing a red fluorescence protein (RFP) gene driven by a VP16-responsive promoter (35). VP16 is in the tegument of HSV-1 virions, a protein layer underneath the envelope but outside the capsid.…”
Section: Resultsmentioning
confidence: 99%
“…Vero Clone 57 cells express RFP under the control of the HSV-1 ICP0 promoter (35). Huh7.5 cells were obtained from C. Rice (The Rockefeller University, New York, NY).…”
Section: Methodsmentioning
confidence: 99%
“…These authors found that emerin hyperphosphorylation depended upon US3 in HSV-2-infected cells and that it could be inhibited by an inhibitor of the cyclin-dependent kinase CDK1. The dependence on CDK1 activity is interesting, since inhibitors of CDKs, including CDK1, inhibit multiple steps in the virus life cycle (8,11,28,(56)(57)(58), and a dominant-negative CDK1 inhibits viral-DNA replication and late-gene expression (1). CDK1 inhibition may depress expression of late genes, and the CDK1 dependence of emerin phosphorylation may reflect lower UL34 expression and recruitment of PKC␦.…”
Section: Discussionmentioning
confidence: 99%